Analysis Of Technical And Legal Norms For The Privatization Of Land Plots - Egamova Dilchehra Adizovna (Zien Journals, 2025)
One of the main goals of the state policy in the field of land relations is to create and ensure conditions for the effective use of state land resources, the introduction of private ownership of land and the creation of a land market. In this regard, the central element of the land reform was the emergence of the right of private ownership of land, its consolidation and guarantee. To date, the privatization process has not been completed, most likely it will take a long time. This article provides information on the technological stages of land privatization, organizational and technical measures carried out on them and their results.
Keywords: land plot; land reform; private property